Understanding the provision of a clinical service in mental health and the role of the pharmacist: a qualitative analysis - Sheilla Alessandra Ferreira Fernandes; Giselle de Carvalho Brito; Aline Santana Dosea; Divaldo Pereira de Lyra Junior; Victoria Garcia-Cardenas; Marta Maria de França Fonteles (Faculdade de Medicina de Botucatu (Unesp), 2021)
Pharmacists have important roles in mental health disease; however, their performance in Brazilian Psychosocial Care Centers (CAPS) is unknown. This qualitative study was conducted in a CAPS, Brazil; using interviews and analyzes from the perspective of Bardin, in which categories arising from the perceptions of patients and the health team emerged in relation to the provision of the medication review with follow up (MR) service and the role of the pharmacist in mental health. According to the participants, the MR service is essential and important because it allows professional recognition, beyond the identification of professional attributes of the pharmacists. Moreover, there was a duality in the pharmacist's role between the logistic and clinical attributes of mental health. Thus, this perception helps to elucidate the pharmacist's process of work in mental health and supports future strategies of action in this area.